Hydrogenation of Carbon Dioxide to Methanol Catalyzed by Iron, Cobalt, and Manganese Cyclopentadienone Complexes: Mechanistic Insights and Computational Design. Issue 37 (15th May 2017) - Ge, Hongyu; Chen, Xiangyang; Yang, Xinzheng
Abstract: Invited for the cover of this issue is the group of Xinzhen Yang at Institute of Chemistry, Chinese Academy of Sciences. The image depicts a series of computationally designed iron, cobalt, and manganese cyclopentadienone catalysts for hydrogenation of carbon dioxide to methanol. Read the full text of the article at10.1002/chem.201701200 . Abstract : " The cover artwork depicts our work as a piano [computational device] playing a melody of the catalytic reaction ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 8850 ff. (DOI:10.1002/chem.201701200 ).